Analysis of The Influence of Information System Applications, Digital Trainings and Technology Adoption on Financial Information System Performance - Arjang; Prakoso, Teguh; Apriliani, Rina; Mertua Agung Durya, Ngurah Pandji; Pattiasina, Victor (SEULANGA SYSTEM PUBLISHER, 2024)
This study intends to investigate how top management support, user training programs, user technical skills, and technology advancements affect the performance of accounting information systems. This study is causal. The study's target demographic consists of retail enterprises implementing computerized systems. Data was gathered using the survey approach, which entailed sending out questionnaires. The sampling method employed is convenience sampling. Multiple linear regressions are employed in hypothesis testing. The study's findings support that technology advancements significantly impact how well the accounting information system functions. These findings align with earlier studies demonstrating how technological sophistication affects information systems' effectiveness, as determined by system utilization and user satisfaction. However, personal technical ability does not significantly influence its performance, in contrast to other research findings that show the opposite. User training programs and top management support have also been shown to dramatically influence AIS performance, following previous research indicating that training programs and management support can improve performance. Other variables not examined in this study explain most of the variation in AIS performance, suggesting the existence of different factors that also play an essential role in determining its performance.